T-Cell Compartmentalization and Functional Adaptation in Autoimmune Inflammation: Lessons From Pediatric Rheumatic Diseases - Mijnheer, Gerdien; van Wijk, Femke (Frontiers in Immunology, 2019)
Chronic inflammatory diseases are characterized by a disturbed immune balance leading to recurring episodes of inflammation in specific target tissues such as the joints in juvenile idiopathic arthritis. The tissue becomes infiltrated by multiple types of immune cell, including high numbers of CD4 and CD8 T cells, which are mostly effector memory cells. Locally, these T cells display an environment-adapted phenotype, induced by inflammation- and tissue-specific instructions. Some of the infiltrated T cells may become tissue resident and play a role in relapses of inflammation. Adaptation to the environment may lead to functional (re)programming of cells and altered cellular interactions and responses. For example, specifically at the site of inflammation both CD4 and CD8 T cells can become resistant to regulatory T cell-mediated regulation. In addition, CD8 and CD4 T cells show a unique profile with pro- and anti-inflammatory features coexisting in the same compartment. Also regulatory T cells are neither homogeneous nor static in nature and show signs of functional differentiation, plasticity and oligoclonality in inflammatory environments. Here we will discuss the recent insights in T cell functional specialization, regulation, and clonal expansion in local (tissue) inflammation.